2023
DOI: 10.3390/buildings13071597
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Architectural Features and Artistic Elements of Traditional Buildings in Different Regions of Jiangxi, China

Abstract: Traditional buildings are a comprehensive manifestation of history, art, and architectural features, and are also a carrier of folk culture, traditional skills, and regional aesthetic tastes. This paper studies traditional buildings and arts from three regions of Jiangxi, including northern Jiangxi, southern Jiangxi, and central Jiangxi. Traditional buildings in Jiangxi Province flourished in the Ming and Qing Dynasties. As Jiangxi is located in the interior of China and is adjacent to many provinces, the arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The emergence of these commercial elements is extremely detrimental to the creation of the traditional atmosphere of historical areas and undermines the continuity of their interfaces. Therefore, concretizing the presentation of environmental colors, which are difficult to capture, also provides an important basis for the selection of modern commercial colors at the interface of historical areas [50]. In the inevitable process of commercialization, it is necessary to maintain the original environmental color of historical areas as much as possible to maintain the authenticity of their historical appearance [51].…”
Section: Discussion On the Application Of Traditional Chinese Colors ...mentioning
confidence: 99%
“…The emergence of these commercial elements is extremely detrimental to the creation of the traditional atmosphere of historical areas and undermines the continuity of their interfaces. Therefore, concretizing the presentation of environmental colors, which are difficult to capture, also provides an important basis for the selection of modern commercial colors at the interface of historical areas [50]. In the inevitable process of commercialization, it is necessary to maintain the original environmental color of historical areas as much as possible to maintain the authenticity of their historical appearance [51].…”
Section: Discussion On the Application Of Traditional Chinese Colors ...mentioning
confidence: 99%
“…Among them, Hui-style architecture is a mature architectural style of ancient Chinese society, which originated in the ancient Huizhou region (Figure 1a). It was widely spread in the upper reaches of the Qiantang River in the Xin'an River basin and is known for its unique style, exquisite carving art, and rigorous structure [3,11]. Huistyle architecture deeply integrates the natural spirit and local customs and culture of Huizhou, showing local characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a vital conduit for China's rich cultural heritage, traditional architectural art not only reflects regional characteristics but also integrates profound cultural, historical, and social dimensions [1]. This study delved into the differences in the impact of Hui-style and Min-style architectures on residents' identities, revealing that these are not only material manifestations of cultural heritage but also potent forces in shaping the personal and social identities of the people living within them [2,3]. With hundreds of years of history, these traditional regional architectures encapsulate the philosophical foundations of social-cultural evolution, economic development, and the spirit of the times within their structure and aesthetics [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…They found that Hakka culture revealed the lifestyle of ancient Chinese people and that Hakka's historical architecture reflected the architectural style of northern China in many aspects (Keith et al, 2013). Wang analyzed the formation of Hakka villages and the characteristics of Hakka historical architecture and discussed how to apply their noble to the protection and sustainable development of Hakka architecture (Song & Liao, 2023). Jin studied the relationship between Hakka culture and Hakka architectural forms through the characteristics of Hakka architecture in Meizhou City, Guangdong Province (Tao et al, 2018).…”
Section: Literature Review 21 Hakka Traditional Architecture In Chinamentioning
confidence: 99%